Willingness to provide informal care to older adults in Germany: a discrete choice experiment - Lea de Jong; Torben Schmidt; Jona Theodor Stahmeyer; Sveja Eberhard; Jan Zeidler; Kathrin Damm (The European Journal of Health Economics, 2022)
As the German population is continually aging and the majority of older adults still wish to 'age in place', the need for informal care provided by family and friends will correspondingly continue to increase. In addition, while the need for formal (professional) care services is also likely to increase, the supply already does not meet the demand in Germany today. The aim of our study is the elicitation of people's willingness to provide informal care by means of a discrete choice experiment. The self-complete postal survey was disseminated to a random sample of the German general population in Lower Saxony. Data cleansing resulted in a final sample size of 280 participants. A conditional logit and a latent class model were estimated. All attributes were judged as highly relevant by the respondents. The results revealed that an increase in the care hours per day had the greatest negative impact overall on the willingness to provide informal care in our sample. The marginal willingness-to-accept for 1~h of informal care was exteuro14.54 when having to provide informal care for 8~h in reference to 2~h per day. This value is considerably higher than the national minimum wage of exteuro9.82. A three-class latent class model revealed preference heterogeneity. While a monetary compensation is often discussed to increase the willingness and availability of informal care in a country, our results show that this statement could not be generalized within our entire sample.
Keywords: C35; I18; J10; J14; 610; Discrete choice experiment; Elderly care; Older adult care; Long-term care; Preferences; Willingness